Epithelial-to-Mesenchymal Transition is Dispensable for Metastasis but Induces Chemoresistance in Pancreatic Cancer - Xiaofeng Zheng,Julienne L. Carstens,Jiha Kim,Kaye Judith,Hikaru Sugimoto,Raghu Kalluri (Macmillan Publishers Limited, 2015)
Diagnosis of pancreatic ductal adenocarcinoma (PDAC) is associated with a dismal prognosis despite current best therapies; therefore new treatment strategies are urgently required. Numerous studies have suggested that epithelial-to-mesenchymal transition (EMT) contributes to early-stage dissemination of cancer cells and is pivotal for invasion and metastasis of PDAC1–4. EMT is associated with phenotypic conversion of epithelial cells into mesenchymallike cells in cell culture conditions, although such defined mesenchymal conversion (with spindle-shaped morphology) of epithelial cells in vivo is rare, with quasi-mesenchymal phenotypes occasionally observed in the tumour (partial EMT)5,6. Most studies exploring the functional role of EMT in tumours have depended on cell-culture-induced loss-of-function and gain-of-function experiments involving EMT-inducing transcription factors such as Twist, Snail and Zeb1 (refs 2,3,7–10). Therefore, the functional contribution of EMT to invasion and metastasis remains unclear4,6, and genetically engineered mouse models to address a causal connection are lacking. Here we functionally probe the role of EMT in PDAC by generating mouse models of PDAC with deletion of Snail or Twist, two key transcription factors responsible for EMT. EMT suppression in the primary tumour does not alter the emergence of invasive PDAC, systemic dissemination or metastasis. Suppression of EMT leads to an increase in cancer cell proliferation with enhanced expression of nucleoside transporters in tumours, contributing to enhanced sensitivity to gemcitabine treatment and increased overall survival of mice. Collectively, our study suggests that Snail- or Twist-induced EMT is not rate-limiting for invasion and metastasis, but highlights the importance of combining EMT inhibition with chemotherapy for the treatment of pancreatic cancer.